Empatía en hermanos de personas con trastorno del espectro autista - Shoji Muñoz, Michelle Stephany (2018)
Fil: Shoji Muñoz, Michelle Stephany. Pontificia Universidad Católica Argentina. Facultad Teresa de Ávila; Argentina